The wishing-chair collection - Blyton, Enid (London: Hodder, 2020)
When Mollie and Peter go to buy their mother a birthday present, they discover the most extraordinary thing: a chair that can fly and grant wishes! The Wishing-Chair takes them on some marvellous adventures - to a castle where they narrowly escape from a giant, to find a pot of gold at the end of the rainbow, and even to help Santa Claus deliver presents for Christmas! Wherever will the wishing-chair take them next? Travel with Mollie, Peter and Binky the pixie and be whisked away on an amazing adventure
Keywords: Fantasy fiction